Análise do impacto da correção cirúrgica na qualidade de vida de 26 pacientes com incontinência urodinâmica de esforço - Pinheiro, Raimundo César (2004)
The Stress Urinary Incontinence is a common problem with impact on the patient’s quality of life. OBJECTIVE- to evaluate the impact on the quality of life of 26 patients with stress urodynamic incontinence that realized vaginal sling and urethrocystopexia of Burch . Quality of life was assessed with the Questionnaire of Impact of Incontinence and the Inventory of Urogenital stress, short forms. METHODS -During the period of March of 2001 to December of 2002 14 patients (group 1) realized vaginal sling and 12 patients (group 2) realized urethrocystopexia of Burch.RESULTS- After a median follow up of nine months (variation of four to 22 months) it was observed an objective cure rate of 96,2% ,twenty five patients, a subjective cure rate of 65,4%, seventeen patients , twenty five patients related cure or improvement after the surgery . At the postoperative periodo it were observed three cases of de novo urgency , patients that realized surgery of Burch, two patients with obstructive urinary dysfunction that made sling and one patient that presented with worsening of incontinence.Some demographic characteristics of the patients : the median age of the patients were of 56 years (variation of 41 to 77 years), the median of the index of corporal mass was of 25 (variation of 20 the 34). The vaginal parity varied from zero to eight childbirths with a median of three childbirths.The hospital stay time varied from two to four days with a median of three days. At the moment of delivery twenty two patients (84,6%) presented with urinary residue equal or less than 100ml. Four patients presented with urinary residue greater than 100ml, one of them had done surgery of Burch and three had done vaginal sling. The median leak point pressure at the preoperative period was of 95 cmH20 (variation of 40 to 140). At the postoperative period it was of 150 cm H20 (variation of 60 the 213). The median score of the Questionnaire of impact of incontinence showed statistically significant difference (p=0,00) between the pre and postoperative period , median of 50 with variation of 10 the 95 and a median of zero with variation of zero to 81 respectively. The median score of the inventory of urogenital stress at the preoperative period was of 53 (variation of 17 the 94), after the surgery it was of six (variation of 16 the 35) wich was statistically significant (p=0,07). The coefficient of the questionnaire of impact of incontinence presented with excellent improvement in twenty-three patients (88,5%), moderate improvement in one patient (3,8%) and worsening in two patients (7,7%). The coefficient of the inventory of urogenital stress presented with excellent improvement in twenty-two patients (84,6%), moderate improvement in two patients (7,7%) and worsening in two patients (7,7%). CONCLUSIONS- The findings of this prospective nonrandomized study showed that objective results not always are correlated with the subjective findings and that the questionnaires of quality of life are valid and important instruments in the evaluation and decision making of patients with stress urodynamic incontinence.